The potential of Cyperus rotundus L. as a natural hair removal agent: A review of traditional and modern applications - Ghada Farouk Mohammed (Phytomedicine Plus, 2025)
Introduction: Hair removal is a fundamental aspect of daily life, with various hair removal methods evolving throughout hair removal history to meet cultural, aesthetic, and spiritual needs. Traditional hair removal practices have long sought effective hair removal products that not only remove hair but also promote skin health. Cyperus rotundus L. (Cr L.), known as nut grass or purple nut sedge, has long been used in traditional medicinal systems like Ayurveda and Traditional Chinese Medicine (TCM) for treating various ailments, including skin conditions and depilation. Aim: to understand the role of Cr L. in decreasing hair growth. Results: Cr L. contains essential oils (EOs) and phytochemicals such as flavonoids, alkaloids, and saponins, which contribute to its hair-removal properties. These compounds target hair follicles, dissolve keratin, and inhibit hair regrowth by modulating biological pathways. γ-curcumene, a key component, has been shown to suppress hair growth. Recent clinical trials have demonstrated the efficacy of Cyperus rotundus essential oil (CREO) in reducing hair growth, with minimal side effects. CREO has been found as effective as Alexandrite laser treatments in some cases, particularly in reducing white hair. This positions Cr L. as a promising natural alternative to chemical depilatories, which often cause skin irritation. Conclusion: Cr L. shows significant potential as a natural hair removal agent. With its strong safety profile and growing consumer demand for natural, sustainable beauty products, Cr L. could serve as a viable alternative to synthetic depilatories, pending further clinical validation.